Perencanaan Dan Perancangan Agrowisata Kelapa Di Desa Gunaksa Kabupaten Klungkung Bali - Komang Arya Surya Nugraha; I Wayan Runa; Gde Bagus Andhika Wicaksana (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Coconut is one of the primary plantation commodities in Indonesia, one of the plantations that boosts the country's economy. Bali is one of the provinces with a reasonably extensive coconut plantation with an annual income of 65,000 tons of raw coconut. Coconut Agrotourism is an educational tourism activity that utilizes coconut plantations as a tourist attraction. The utilization of this business in the plantation sector includes processing coconuts from the plantations of residents so that they become products with national and even international selling values. In other words, the products produced can not only be enjoyed by the domestic community but can also be enjoyed by outsiders. Not only are processed products served, but experience, understanding, and knowledge about coconut or coconut plantations are also presented as a means of education. Coconut Agrotourism is developed by utilizing the potential of both natural resources and human resources.